EVALUASI KERASIONALAN PENGOBATAN DIABETES MELITUS TIPE 2 PADA PASIEN RAWAT INAP DI RUMAH SAKIT BHAKTI WIRA TAMTAMA SEMARANG TAHUN 2006 - ibrahim arifin; erna prasetyaningrum; tri murti andayani (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2007)
ASTRACTDiabetes melitus is metabolic disease characterized hiperglikemia that caused disparity of insulin secretion, insulin activity or both. WHO had predicted there were increasing of diabetes mellitus patients in next time, included in Indonesia. This study aim to know and evaluate the rational of in patients diabetes mellitus type 2 medication in Bhakti Wira Tamtama Hospital Semarang at 2006. This study is non experimental research that analyzed by non analytical descriptive method. Data were collected retrospectively from medical record comprised patient identity, diabetes melitus type 2 medication, and rational antidibetic usage. Data obtained were analysed with Standard of Perkeni 2006. The result of this study showed that 34 in-patient diabetes mellitus type 2 in Bhakti Wira Tamtama Hospital Semarang at 2006 were 40-50 years old (47,06%). Diabetes mellitus type 2 patients comprised 18 men and 16 women, 8 cases (23,52 %) were diabetes mellitus type 2 without additional diseases and 26 cases (76,47%) diabetes mellitus type 2 with additional diseases. Patients had diagnosis appropriate were 94,12 %, drug choise appropriate were 100 %, which biguanid metformin usage were 15 patients (46,87%). Dosis appropiate 100%, patient appropriate 100%, while drug interaction had happened to 1 case, that was antidiabetic and thiazid diuretic. Key words: Rational evaluation, diabetes mellitus type 2, Bhakti Wira Tamtama Hospital Semarang